The Influence of a Scientific Approach with Fun Science on Learning Motivation and Understanding of Physics Concepts - Gultom, Roidah Aryani; Imran, Ali; Sibagariang, Muhammad Taufik (Gravity Journal, 2024)
The objective of this study is to know about the influence of learning Science using scientific approach with fun science to learning motivation of JUNIOR HIGH SCHOOL students, the influence of learning Natural Science using scientific approach with fun science towards an understanding of the concept of Natural Science of JUNIOR HIGH SCHOOL students, and the influence of learning Natural Science using scientific approach with fun science to learning motivation and understanding of the concept of Natural Science of JUNIOR HIGH SCHOOL students. The object of this research is the VII grade students with "change in physics and chemical changes" learning material. This is a quasi experiment research with Pretest-Posttest Nonequivalent Control Group Design conducted in SMP Negeri 1 Panyabungan Utara . The sample in this research were determined with cluster random sampling techniques, therefore it resulted VII A class as the control class and VII B class as the experimental class. The treatment given to the experimental class was using scientific approach to learn with fun science (blobs in a bottle, ice cream, rapid color-changing chemistry, and merapi vulcano), while in the control class was the implementation of EEK learning-based (exploration, Elaboration, and confirmation). The students’ learning motivation data was obtained using students’ learning motivation observation sheets. The students’ understanding of Natural Science data were collected by giving tests before (pretest) and after (posttest) learning. The Hypothesis testing was done by using a manova test after the test met the prerequisites. A prerequisite tests conducted were normality tests and homogeneity test. The results showed that learning using scientific approach with fun science has significantly impact on the students’ learning motivation and understanding concept of Natural Science. The influence of the scientific approach with fun science learning motivation up to 20,1% by average grade learning motivation experiments reached category enough. Scientific approach with fun science also has an impact on the students’ understanding of the concept of Natural Science up to 24,2% with an average increased to reached the category medium.